2018
DOI: 10.1111/jopy.12393
|View full text |Cite
|
Sign up to set email alerts
|

Internet trolling and everyday sadism: Parallel effects on pain perception and moral judgment

Abstract: Results confirm that online trolling is motivated (at least in part) by sadistic tendencies. Coupled with effective rationalization mechanisms, sadistic pleasure can be consummated in such everyday behaviors as online trolling.© 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 69 publications
5
87
1
4
Order By: Relevance
“…The concept of FOMO (fear of missing out) fits quite well in this chain as this fear often leads to insecurity and to avoid that the individual tries to escape from reality by spending more time on the internet. As per a recent study (Buckels, 2018), it has been found that internet trolls are way more likely to be sadists, psychopaths and narcissists. An internet troll is a person who contributes to (online) discussions or post comments in such a way that it upsets or disrupts the conversation.…”
mentioning
confidence: 72%
“…The concept of FOMO (fear of missing out) fits quite well in this chain as this fear often leads to insecurity and to avoid that the individual tries to escape from reality by spending more time on the internet. As per a recent study (Buckels, 2018), it has been found that internet trolls are way more likely to be sadists, psychopaths and narcissists. An internet troll is a person who contributes to (online) discussions or post comments in such a way that it upsets or disrupts the conversation.…”
mentioning
confidence: 72%
“…Based on the collective research of the Dark Tetrad traits and sexual abuse, it is suggested that they may also be associated with TFSV perpetration. Additionally, recent research has shown that individuals with dark personality traits are more likely to engage in comparably deviant online behaviours like online trolling, a form of cyber-harassment intended to aggravate, annoy or otherwise disrupt online communications (e.g., Binns, 2012;Buckels et al, 2019;Buckels et al, 2014;Craker & March, 2016;Lopes & Yu, 2017), and high levels of sadism are associated with greater enjoyment associated with such behaviours (Buckels et al, 2014). In a study on technology facilitated infidelity, non-single Tinder users were found to score significantly higher on psychopathic traits than non-single non-users (Timmermans et al, 2018).…”
Section: Dark Tetrad Personality Traitsmentioning
confidence: 99%
“…These phenomena can create a real and damaging link between online and real-life behaviors [71,73,74]. Aggressive online behaviors have been categorized into subtypes, which include hostile aggression (e.g., "an act of aggression stemming from a feeling of anger and aimed at inflicting pain or injury") and instrumental aggression (e.g., "an intention to hurt the other person, but the hurting takes place as a means to some goal other than causing pain") [75]. Within this general context, SM facilitates and escalates negative behaviors that may serve to "deliver aggression," while not being physically present, yet directed toward the person of interest.…”
Section: Social Media Platforms: "Weaponizing" Human Emotions and Intmentioning
confidence: 99%